Cognitive demands during quiet standing elicit truncal tremor in two frequency bands: differential relations to tissue integrity of corticospinal tracts and cortical targets - Sullivan, Edith V.; Zahr, Natalie M.; Rohlfing, Torsten; Pfefferbaum, Adolf (Frontiers in Human Neuroscience, 2015)
The ability to stand quietly is disturbed by degradation of cerebellar systems. Given the complexity of sensorimotor integration invoked to maintain upright posture, the integrity of supratentorial brain structures may also contribute to quiet standing and consequently be vulnerable to interference from cognitive challenges. As cerebellar system disruption is a common concomitant of alcoholism, we examined 46 alcoholics and 43 controls with a force platform to derive physiological indices of quiet standing during cognitive (solving simple, mental arithmetic problems) and visual (eyes closed) challenges. Also tested were relations between tremor velocity and regional gray matter and white matter tissue quality measured with the diffusion tensor imaging (DTI) metric of mean diffusivity (MD), indexing disorganized microstructure. Spectral analysis of sway revealed greater tremor in alcoholic men than alcoholic women or controls. Cognitive dual-tasking elicited excessive tremor in two frequency bands, each related to DTI signs of degradation in separate brain systems: tremor velocity at a low power (2-5 Hz/0-2 Hz) correlated with higher MD in the cerebellar hemispheres and superior cingulate bundles, whereas tremor velocity at a higher power (5-7 Hz) correlated with higher MD in the motor cortex and internal capsule. These brain sites may represent "tremorgenic networks" that when disturbed by disease and exacerbated by cognitive dual-tasking contribute to postural instability, putting affected individuals at heightened risk for falling.